2019
DOI: 10.1177/1558944719836213
|View full text |Cite
|
Sign up to set email alerts
|

Supercharge End-to-Side Nerve Transfer: Systematic Review

Abstract: Background: To decrease the time to reinnervation of the intrinsic motor end plates after high ulnar nerve injuries, a supercharged end-to-side (SETS) anterior interosseous to ulnar motor nerve transfer has been proposed. The purpose of this study was to compile and review the indications, outcomes, and complications of SETS anterior interosseous to ulnar motor nerve transfer. Methods: A literature search was performed, identifying 73 papers; 4 of which met inclusion and exclusion criteria, including 78 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
22
1
2
Order By: Relevance
“…12 A meta-analysis by Dunn et al showed that ETS yielded a high return of intrinsic function in 91.9% patients at 3.7 months and 8% did not recover intrinsic strength. 10 Our patient had no functional deficit on review at 3 months. The ETS anterior interosseous-to-ulnar nerve transfer may be a useful technique for augmenting intrinsic muscle function for severe, in continuity lesions of the ulnar nerve where limited surgical options exist.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…12 A meta-analysis by Dunn et al showed that ETS yielded a high return of intrinsic function in 91.9% patients at 3.7 months and 8% did not recover intrinsic strength. 10 Our patient had no functional deficit on review at 3 months. The ETS anterior interosseous-to-ulnar nerve transfer may be a useful technique for augmenting intrinsic muscle function for severe, in continuity lesions of the ulnar nerve where limited surgical options exist.…”
Section: Discussionmentioning
confidence: 58%
“…9 Wide local excision of the tumour is the treatment of choice followed by thorough biopsy and additional excision if necessary. 10 In high grade lesions, prognosis is grim and chemotherapy and radiation are the only methods of controlling the cancer. 4 Functional compromise that can occur while giving adequate clearance margin for the tumor is common, however microsurgical techniques and neuroanastomosis provide the patient with better prognosis along with preserving function.…”
Section: Discussionmentioning
confidence: 99%
“…After analysis of the 78 patients from the 4 studies, they concluded that the supercharge end-to-side transfer (SETS) of the anterior interosseous nerve (AIN) to the motor branch of the ulnar nerve (MUN) had yielded a high return of intrinsic function of 91.7 % at an average of 3.7 months. 1 These results must be interpreted with caution. Such a rapid and complete recovery is typical of incomplete lesions or aberrant median-to-ulnar intrinsic innervation.…”
Section: Letter To the Editormentioning
confidence: 98%
“…The patients included have a mixed etiology of compressive, inflammatory, and traumatic lesions of the ulnar nerve, as well as a variety of adjunctive procedures. [1][2][3][4] This would make interpretation of the results difficult, and we feel that traumatic lesions should be a separate subgroup from compressive lesions. A further concern is that 2 of the 4 papers included in the systematic review were not papers about SETS transfers, but used a standard end-to-end (ETE) transfer technique.…”
Section: Letter To the Editormentioning
confidence: 98%
See 1 more Smart Citation